What Is the Cost of Off-Axis Insertion of Locking Screws? A Biomechanical Comparison of a 3.5 mm Fixed-Angle and 3.5 mm Variable-Angle Stainless Steel Locking Plate Systems - Kaczmarek, Jakub; Bartkowiak, Tomasz; Paczos, Piotr; Zawadzki, Paweł; Łączna, Daria; Gapiński, Bartosz (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to evaluate the effect of screw insertion angle and insertion torque on the mechanical properties of a 3.5 fixed-angle locking plate locking compression plate (LCP) and 3.5 variable-angle locking plate polyaxial locking system (PLS).Methods In the LCP group, screws were placed abaxially at 0, 5 and 10 degrees. In the PLS group, screws were placed at 0, 5, 10, 15 and 20 degrees abaxially. The insertion torque was set to 1.5 and 2.5 Nm in the LCP and PLS groups respectively. A load was applied parallel to the screw axis, and the screw push-out force was measured until the locking mechanism was loosened.Results The 3.5 LCP showed higher push-out strength than the 3.5 PLS when the screws were placed at 0 degree regardless of the insertion torque. The off-axis insertion of 3.5 LCP locking screws resulted in a significant decrease in push-out strength (p < 0.05). A higher insertion torque value significantly increased the screw holding strength for the 3.5 LCP (p < 0.05). The 3.5 PLS system had a significantly higher push-out force when the screws are at 0 degree than at 5, 10 and 15 degrees, and 20 degrees (p < 0.05) at any given insertion torque. An increase in the insertion torque did not have a significant effect on the push-out strength of the 3.5 PLS locking system.Conclusion The 3.5 PLS is more sensitive to the screw insertion angle than to the insertion torque, whereas the 3.5 LCP is affected by both factors. Placing 3.5 LCP locking screws off-axis significantly reduces the screw holding strength; therefore, this approach has to be avoided. The findings of our research indicate that a 1.5 Nm torque can be used for a 3.5 PLS.
Keywords: polyaxial; locking screw; locking plate; insertion angle; insertion torque